Comparison of nonsurgical periodontal therapy with oral hygiene instruction alone for chronic periodontitis - Maaz Asad; Alwani W. Abdul Aziz; Renukanth P. C. Raman; Himratul-Aznita W. Harun; Tara Bai T. Ali; Karuthan Chinna; Rathna D. Vaithilingam (Nihon University School of Dentistry, 2024)
Indexed by SCOPUS